Value of laboratory investigation data for the diagnostic of acute appendicitis in children - A.A. Pereyaslov; O.M. Nykyforuk; A.I. Bobak; R.V. Stenyk; R.I. Dats; B.Y. Malovanyy (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2020)
Introduction. Despite of the long history of acute appendicitis study, the frequency of delayed diagnosis, perforative AA, and negative appendectomy remains high. Diagnosis of acute appendicitis in a lot of cases dependent of surgeons' clinical experience, besides that for the most part of patients the typical clinical presentation is absent, that determine the rather high frequency of the diagnostic mistakes and necessity to find new diagnostic markers. Aim of the study was to compare the various laboratory markers not only for diagnostic of acute appendicitis, but also for preoperative selection of patients with possible perforative appendicitis. Material and Methods. This study based on the results of surgical treatment of 3171 children with acute appendicitis, which were operated in 1st surgical department of Lviv regional clinical hospital «OXMATDYT» during 2009-2018 years. The control group complain 146 children with suspected diagnosis of acute appendicitis, but subsequently this diagnosis was rejected. Receiver operating characteristic curve, specificity, sensitivity, positive prognostic value (PPV) and negative prognostic value (NPV), likelihood ratio (LR) were determined for leukocytes and neutrophils count, neutrophils to lymphocytes ratio (NLR) for the acute appendicitis diagnostic and appendix perforation, and sodium level for perforated appendicitis. Results and discussion. The best predictive value for the diagnosis of acute appendicitis displayed NLR (sensitivity - 84.9%, specificity - 67.1%, PPV - 17%, NPV - 98.2%, LR(+) - 2.58, LR(-) - 0.23) and neutrophils count (sensitivity - 73.5%, specificity - 69.2%, PPV - 10.7%, NPV - 98.1%, LR(+) - 2.39, LR(-) - 0.38), but leucocytes count do not have such predictive value. For the preoperative diagnosis of perforated appendicitis, the most significant results received for NLR (sensitivity - 90.3%, specificity - 89.9%, PPV - 98.9%, NPV - 46.4%, LR(+) - 8.94, LR(-) - 0.11) and blood sodium level (sensitivity - 82.5%, specificity - 84%, PPV - 98.5%, NPV - 27.5%, LR(+) - 5.20, LR(-) - 0.20). Conclusion. Among markers of complete blood count, the best prognostic value for the diagnosis of acute appendicitis in children, have NLR and neutrophils count. NLR and sodium blood level permit with the high degree of reliability preoperatively select patients with suspected appendix perforation.